Revision of the Megaphyllum projectum Verhoeff species complex (Myriapoda: Diplopoda: Julida: Julidae) - Lazányi, Eszter; Korsós, Zoltán (Zootaxa, 2011)
On the basis of male and female genitalia and nonsexual morphology, the revision of Megaphyllum projectum Verhoeff, 1894 and of its five nominal subspecies (M. p. projectum Verhoeff, 1894, M. p. alticolum Verhoeff, 1897, M. p. deubeli Verhoeff, 1899, M. p. kochi Verhoeff, 1907, M. p. dioritanum Verhoeff, 1907) has been carried out. The forms deubeli and kochi proved to be valid subspecies, while the other two forms are synonymised with the nominotypical subspecies, M. p. projectum. The differences in the male gonopod of M. p. dioritanum from the nominotypical subspecies projectum are only due to its positioning under the microscope, while M. p. alticolum showed also only minor differences from projectum, so it cannot be considered as separate subspecies. Female genitalia also seem to support the existence of the three subspecies. A short key for the subspecies is included.